Scattering process in the Scalar Duffin-Kemmer-Petiau gauge theory - Beltran, J. [UNESP]; Pimentel, B. M. [UNESP]; Soto, D. E.; IOP (Iop Publishing Ltd, 2016)
In this work we calculate the cross section of the scattering process of the Duffin-Kemmer-Petiau theory coupling with the Maxwell's electromagnetic field. Specifically, we find the propagator of the free theory, the scattering amplitudes and cross sections at Born level for the Moeller and Compton scattering process of this model. For this purpose we use the analytic representation for free propagators and take account the framework of the Causal Perturbation Theory of Epstein and Glaser.